Contenido informativo en la red social TikTok: estudio de caso La Quinta Pata @la5pata_ec. - Flores Vite, Andrés Alejandro (2023)
The media have transferred their content to social networks with the intention of gaining new audiences, which has modified communication models. Such is the case of the social network TikTok, which began as a purely entertainment platform, but the installation of media in the Chinese social network modified it and now informative content is also part of it. In this sense, a guide to information dissemination strategies for media on TikTok was developed based on the content of the media La Quinta Pata. It should be noted that it is an Ecuadorian digital media outlet with more than 659 thousand 'followers' and a total of around 36.4 million likes. Thus, through content analysis, the new narratives were studied and user interaction was identified, which led to the design of strategies aimed at managing TikTok for the media. Among the main results, it was detected that on TikTok content with vertical and short duration format predominates, averaging between 36 to 39 seconds as ideal to feed the platform. Furthermore, entertainment is the topic with the greatest interaction, the reverse is the case with the topics of politics and economics, which despite having their space, are part of the group with the least response from users. It should be said that the strategies proposed in this project are a contribution for the media with an interest in disseminating informative content on the Chinese platform.